The development of Key Performance Indicator [KPIs] at aerospace manufacturing company / c Effendi bin Mohamad - Effendi Mohamad (Penerbit Universiti Teknikal Malaysia Melaka, 2009)
The title of this study is "The development of Key Performance Indicator [KPIs] at aerospace manufacturing company". This study focuses on the issue of the KPIs development which is linked to the goal, objective, mission and vission of ABC Company.